A proof-of-concept application of water-soluble ytterbium(iii) molecular probes in in vivo NIR-II whole body bioimaging. Issue 8 (29th May 2019) - Ning, Yingying; Chen, Si; Chen, Hao; Wang, Jing-Xiang; He, Shuqing; Liu, Yi-Wei; Cheng, Zhen; Zhang, Jun-Long
Abstract : Lanthanide complexes are firstly applied for in vivo NIR-II high resolution whole body bioimaging. Abstract : Near-infrared (NIR) emissive lanthanide (Ln) complexes are promising candidates for fluorescence imaging in the NIR-II region (1000–1700 nm) to combine the advantages of small organic molecules and inorganic metal ions. However, their metabolism in vivo and application in in vivo imaging are still unknown. In this work, we used water-soluble Yb 3+ molecular probes with a quantum yield of ca. 10% in water, which showed a deep penetration (>3 mm) upon excitation at the Q band. One of the Yb 3+ complexes, Yb-2, was successfully applied in high resolution non-invasive whole body, vasculature and lymph node imaging of small animals. The complex cleared from the body through hepatobiliary and renal systems, similar to most organic fluorophores. Importantly, we demonstrated the application ofYb-2 in fluorescence-guided sentinel lymph node surgery, showing the prospective application of lanthanide complexes as molecular probes in NIR-II whole body bioimaging and surgical operation.